True Amino Acid Digestibility of Fermented Shrimp Waste in Broiler Chicks - Djunaidi, I.H.; Hardini, D. (International Journal of Poultry Science, 2010)
Thirty 55 days old of MB-202 male broiler chicken were used in a completely randomized design to evaluate the digestibility of Aspergillus sp. fermented shrimp waste (FSW) by force feeding technique. There were 4 dietary treatments, each having 6 replicates. Three diets each of A. niger FSW (FSWn) , A. oryzae FSW (FSWo) and A. sojae FSW (FSWs) were formulated and one raw SW diets as control. The birds were fasted for 24 h and force feeding as quickly as possible and total excreta sampling for amino acids digestibility evaluation. The amino acid digestibility of FSW groups were higher as compared to the raw SW. Among FSW groups treatment, the digestibilities FSWn were higher for all amino acid. Supplementation of the diets with lysine have more attention in order to utilization of FSW as broiler feedstuff.